MOLECULAR ADVANCES IN SEMEN QUALITY ASSESSMENT AND IMPROVING FERTILITY IN BULLS - A REVIEW - BINSILA, B K; SELVARAJU, S; SOMASHEKAR, L; ARCHANA, S S; ARANGASAMY, A; RAVINDRA, J P; BHATTA, R (The Indian Journal of Animal Reproduction, 2022)
Fertility is declining in domestic animals across the world. The reduction in fertility could be attributed tomale, female and managemental factors. Although artificial insemination (AI) using frozen semen emerged 50years back, fertility rate with AI technology is less and unpredictable. In AI industry, one bull is used to produce atleast three lakh insemination doses; hence, the selection of fertile bulls becomes very important. Since standardsemen evaluation tests are not sufficient to predict bull fertility accurately, the researchers have sought laboratoryassays / molecular tests that would accurately predict the fertilizing potential of a semen sample. In this context,biotechnological advances in “omic technologies” help to understand the events associated to spermatogenesis,sperm function, fertilization and embryonic development ending in birth of viable healthy offspring. Profilingfertility-regulating biomolecules substances in spermatozoa or seminal plasma are considered to be helpful topredict fertility.
Keywords: Bull fertility; Metabolomics; Proteomics; Sperm quality; Transcriptomics